Effect of Oseltamivir Use on Follow-Up Stroke Mortality - Pei-Hua Chuang; Bor-Show Tzang; Chih-Chen Tzang; I-Ying Kuo; Chun-Yu Lin; Tsai-Ching Hsu (Pharmaceuticals, 2025)
Background/Objectives: Evidence has indicated an increased risk of stroke in individuals with influenza infection, and the administration of Oseltamivir revealed a lower stroke risk in these individuals. However, the impacts of Oseltamivir and stroke remain limited. Methods: The data used in this retrospective cohort study were extracted from the Taiwan National Health Insurance Research Database (NHIRD), which included 281,420 Oseltamivir users and 13,394,652 patients between 1 January 2009 and 31 December 2018. The Oseltamivir group was younger (age 40.1 ± 15.3 years) and had a lower prevalence of comorbidities compared to the non-user group (age 46.2 ± 16.0 years). Stroke incidence and mortality were compared using multivariable Cox proportional hazards models. Results: We compared the incidence of ischemic stroke among individuals without a history of ischemic stroke, stratified by Oseltamivir use. After adjusting for age, sex, and comorbidities, Oseltamivir use was not associated with a significantly different risk of stroke (adjusted HR = 1.02, 95% CI: 0.96–1.08; p = 0.511). The mortality among individuals with a history of ischemic stroke, being Oseltamivir users (n = 2502), exhibited a lower cumulative mortality rate compared to non-users (4.08% vs. 6.45%). The association remained significant after multivariable adjustment, with an adjusted hazard ratio for mortality of 0.74 (95% CI: 0.61–0.89; p = 0.002). Conclusions: In this large population-based cohort of patients without a history of ischemic stroke, Oseltamivir use during influenza infection was not associated with stroke incidence after adjusting for age, sex, and comorbidities. Notably, Oseltamivir use in patients with a history of ischemic stroke was associated with reduced all-cause mortality, suggesting a potential survival benefit that warrants further investigation.